Synthesis of Thinned Planar Concentric Circular Antenna Arrays Using a Modified Artificial Bee Colony Algorithm - Sun, Yuqi; Sun, Jianbang; Ye, Lei (International journal of antennas and propagation, 2023)
The artificial bee colony (ABC) algorithm is a biomimetic optimization algorithm based on the intelligent foraging behavior of a bee colony. It has obvious advantages in dealing with complex nonlinear optimization problems. However, the random neighborhood search leads to the ABC algorithm being good at exploration but neglected in exploitation. Therefore, a modified artificial bee colony algorithm (MABC) is proposed in this paper. The modified artificial bee colony algorithm is applied to the thinned optimization of large multiple concentric circular antenna arrays. The aim is to make the thinned array obtain the narrow beam pattern with the best peak sidelobe level (PSLL) in the vertical plane. The elements in the concentric circular antenna arrays are uniformly excited and isotropic. Two different cases have been considered in this study for thinning of concentric circular antenna arrays using MABC, one with fixed uniform interelement spacing and another with optimum uniform interelement spacing. In both the cases, the thinning percentage of the array is kept equal to or more than 50%. Simulation results of the proposed thinned arrays are compared with a fully populated array to illustrate the effectiveness of our proposed method.